Pyocyanin-dependent electrochemical inhibition of Pseudomonas aeruginosa biofilms is synergistic with antibiotic treatment - Fernanda Jiménez Otero; Dianne K. Newman; Leonard M. Tender (mBio, 2023)
ABSTRACT Pseudomonas aeruginosa biofilms are common in chronic wound infections and recalcitrant to treatment. Survival of cells within oxygen-limited regions in these biofilms is enabled by extracellular electron transfer (EET), whereby small redox active molecules act as electron shuttles to access distal oxidants. Here, we report that electrochemically controlling the redox state of these electron shuttles, specifically pyocyanin (PYO), can impact cell survival within anaerobic P. aeruginosa biofilms and can act synergistically with antibiotic treatment. Prior results demonstrated that under anoxic conditions, an electrode poised at sufficiently oxidizing potential (+100 mV vs Ag/AgCl) promotes EET within P. aeruginosa biofilms by re-oxidizing PYO for reuse by the cells. Here, when a reducing potential (−400 mV vs Ag/AgCl) was used to disrupt PYO redox cycling by maintaining PYO in the reduced state, we observed a 100-fold decrease in colony forming units within these biofilms compared with those exposed to electrodes poised at +100 mV vs Ag/AgCl. Phenazine-deficient Δphz* biofilms were unaffected by the potential applied to the electrode but were re-sensitized by adding PYO. The effect at −400 mV was exacerbated when biofilms were treated with sub-MICs of a range of antibiotics. Most notably, addition of the aminoglycoside gentamicin in a reductive environment almost completely eradicated wild-type biofilms but had no effect on the survival of Δphz* biofilms in the absence of phenazines. These data suggest that antibiotic treatment combined with the electrochemical disruption of PYO redox cycling, either through the toxicity of accumulated reduced PYO or the disruption of EET, or both, can lead to extensive killing. IMPORTANCE Biofilms provide a protective environment but also present challenges to the cells living within them, such as overcoming nutrient and oxygen diffusion limitations. Pseudomonas aeruginosa overcomes oxygen limitation by secreting soluble redox active phenazines, which act as electron shuttles to distal oxygen. Here, we show that electrochemically blocking the re-oxidation of one of these electron shuttles, pyocyanin, decreases cell survival within biofilms and acts synergistically with gentamicin to kill cells. Our results highlight the importance of the role that the redox cycling of electron shuttles fulfills within P. aeruginosa biofilms.